A new species of the hoplichthyid genus Hoplichthys (Teleostei: Hoplichthyidae) from northern Western Australia - Nagano, Yuki; Mcgrouther, Mark A.; Yabe, Mamoru (Zootaxa, 2013)
A new species of hoplichthyid, Hoplichthys imamurai, is described on basis of three specimens (128.9–143.6 mm SL) collected from northern Western Australia. It is clearly distinguished from its congeners by the following combination of characters: short preoptic snout (31.2–32.7% HL); vomer without teeth; long, thin, gill rakers; low first dorsal fin, its ad-pressed tips not reaching origin of second dorsal fin in males; some filament-like elongated second dorsal-fin rays in males; emarginate caudal fin, upper edge elongated and filament-like in males. Toothless vomer and form of caudal fin are characters unique to H. imamurai in this genus.